Scaphoid fracture geometrics: an assessment of location and orientation. Issue 3 (4th May 2019) - Garala, Kanai; Dias, Joseph
Abstract: The location and angle of scaphoid fractures are important attributes which guide management. We used a 3 dimensional scaphoid model, generated from CT scans, to map scaphoid fracture planes. The point at which the fracture plane crossed the central axis of the scaphoid was noted. The angle of the fracture planes with regard to the central axis was also noted. This allowed calculation of the location of the fracture and the angle of the 379 fractures. The mean point of intersection for fractures with the scaphoid axis was 50% along the scaphoid. Sixty percent of all fractures were found around the central 20% of the scaphoid. The mean angle between the scaphoid axis and the fracture plane was 63 degrees). On comparing angle with location, as fractures move away from the scaphoid waist, they become less perpendicular to the scaphoid axis ( p < .01). Older patients are more likely to have proximal fractures ( p < .01). Men are more at risk of proximal scaphoid fractures than women ( p < .001). Proximal fractures increases risk of progressing to non-union ( p = .018). There was no link between fracture plane angles and age, sex and union status. Most fractures occur at the centre of the scaphoid. There is a link between the location and angle of scaphoid fractures. It also identifies older patients and males are more likely to have more proximal scaphoid fractures.